Early treatment of anterior crossbite with eschler appliance: Two case reports - Kamila de Oliveira Novais Machado; Dauro Douglas Oliveira; Andre Wilson Machado (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Anterior Crossbite (AC) originates from skeletal alterations, functional, dental or their association, and may have genetic and/or environmental influences. Its prevalence varies between 2.2% and 12% depending on age, ethnicity and the type of AC. During the primary dentition, it varies between 4% and 7%. The aim of this paper is to present two clinical cases of anterior crossbite correction in the primary dentition, in which the Eschler appliance was chosen for both treatments.